Representation and partnership: a case study of the worker committee on fair trade certified farms in the Ecuadorian cut-flower industry - Schelly, Erica, author; Raynolds, Laura, advisor; Murray, Doug, committee member; Stevis, Dimitris, committee member (Colorado State University. Libraries, 2011)
This thesis explores the effectiveness of the worker committee on fair trade certified flower plantations in Ecuador in an effort to identify the challenges and opportunities for fair trade in its goal to facilitate worker representation and empowerment on large-scale enterprises. Representation starts by giving workers an institutional mechanism through which they can join management in the discussion of fair working conditions. The worker committee serves as this mechanism on certified farms in Ecuador. Empowerment implies that workers have the power to instigate change in order to improve working conditions. Providing worker empowerment is problematic in this context due to the structural limitations of the worker committee. Nonetheless, the extent to which the worker committee can provide representation and communication between workers and management may serve as an important step in the process towards worker empowerment. In order to understand the potential for representation on flower plantations, it is important to acknowledge that the flower industry and the actors involved are operating in a market that favors rationality and productivity. I employ Weber's notion of formal rationality to help situate this discussion. Formal rationality is the governing force behind the rise of modern society and its institutions; including the modern global economy. Formal rationality allows for efficiency and calculability, but also leads to an impersonal world where the needs of individuals are sidestepped in order to create a system of productivity. The goal of this study is to demonstrate how management's drive to rationalize production in order to survive in a competitive flower industry has the potential to both constrain and enable the process toward worker empowerment. For flower producers, the drive to differentiate makes certification an attractive option. Certified farms in turn, provide the institutional space for worker representation and communication with management. This paper argues that representation is a precondition for the type of empowerment that workers ultimately need, but does not assume that representation and empowerment are synonymous. Specifically, this study looks at the potential benefits and limitations of the worker committee in its effort to facilitate representation and communication. It addresses two research questions. What are the rationalization processes that impact the lives of workers and managers? To what extent does the worker committee serve as a forum for communication between workers and managers to promote representation?
Keywords: Ecuador; worker committees; flowers; fair trade